An Evaluation of The Compilation of a Country-Specific Mandarin Textbook: Tourism and Hotel Management for Special Purposes: 国别化“华语课本：旅游和酒店管理科专用”编写评析 - Low Hiang Loon (Published by Confucius Institute UNS, 2024)
Driven by the “One Belt One Road Initiative”, Malaysia has a huge Chinese tourist market. In cultivating non-native Chinese to provide tourism and hotel services for Chinese tourists, does Malaysian country-specific